2016
DOI: 10.1038/srep36663
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting MDSC differentiation from bone marrow with phytochemical polyacetylenes drastically impairs tumor metastasis

Abstract: Myeloid-derived suppressor cells (MDSCs) are implicated in the promotion of tumor metastasis by protecting metastatic cancerous cells from immune surveillance and have thus been suggested as novel targets for cancer therapy. We demonstrate here that oral feeding with polyacetylenic glycosides (BP-E-F1) from the medicinal plant Bidens pilosa effectively suppresses tumor metastasis and inhibits tumor-induced accumulation of granulocytic (g) MDSCs, but does not result in body weight loss in a mouse mammary tumor-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 49 publications
0
18
0
3
Order By: Relevance
“…Bone marrow is rich in mononuclear cells containing CD11b+Gr-1+ cells. Various research has indicated that bone marrow is the major source of CD11b+Gr-1+ cells [23]. However, the spleen contains numerous monocytes or promonocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow is rich in mononuclear cells containing CD11b+Gr-1+ cells. Various research has indicated that bone marrow is the major source of CD11b+Gr-1+ cells [23]. However, the spleen contains numerous monocytes or promonocytes.…”
Section: Discussionmentioning
confidence: 99%
“…MDSCs have now been categorized into two distinctive subtypes. These are the monocytic MDSCs and granulocytic MDSCs (M-MDSCs and G-MDSCs) [3].…”
Section: Introductionmentioning
confidence: 99%
“…This factor is principally required for the differentiation of M-MDSCs. Also, tumor-derived Granulocyte-Macrophage Colony-Stimulating Factor (GM-CSF) has demonstrated to partake in M-MDSC generation [3,6]. Nevertheless, the proportion of G-MDSC to M-MDSC in diverse cancer models is extremely unpredictable and relies on factors that still need further investigation into.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations